Protective effect of resveratrol against corticosterone-induced neurotoxicity in PC12 cells - Zhang Ye (De Gruyter, 2019)
Resveratrol(RES) is a natural polyphenol which possesses an anti-depressant effect. However, the mechanisms of its anti-depressant effect remain unclear. The aim of the study is to investigate the potential mechanisms in the neuro-protective efficiency in the corticosterone-induced pheochromacytoma 12 (PC12) cells.